On Estimates of Deviation of Functions from Matrix Operators of Their Fourier Series by Some Expressions with r-Differences of the Entries - Włodzimierz Łenski; Bogdan Szal (Abstract and Applied Analysis)
We generalize the results of Krasniqi 2012 and Wei and Yu 2012 to the case of r-differences.